Developing an observation methodology for non-measurable rotorcraft states - Trainelli, L.; Riboldi, C.E.D.; Salucci, F. (My University, 2017)
A recurring problem in engineering is that of observing quantities which cannot be directly acquired through a measuring instrument. For the case of rotorcraft, such quantities include the thrust coefficient and the angle of attack of the tip-path plane. These variables can be profitably exploited to predict the acoustic footprint of the vehicle on the ground, thus helping in designing and monitoring appropriate approach maneuvers, suitable for reducing perceived noise for overflown communities. In previous works on the topic, it was shown how to construct an observer based on real-time measurements of rotor flapping and a few other aeromechanical quantities, capable of estimating key unmeasurable parameters, with an airspeed-scheduled linear structure. Theoretical support comes from a very straightforward model of the helicopter flight mechanics and of the blade flapping motion. Testing on the proposed observer have been carried out during specific descent profiles only, showing the validity of the concept. The present paper tries to expand the analysis to a wider array of test cases, emending the original design in the process. In particular the analysis is extended to a broader spectrum of airspeeds, coping with the non-linear behavior of rotorcraft flight mechanics and rotor flapping dynamics. The effect of an augmentation of the array of measures with more parameters commonly available from the helicopter data bus on the performance of the observer is quantified. The chance to obtain further observed measures, in particular the sideslip angle, from the same set of measurements is considered. Finally, the observer is tested in off-design conditions, in order to assess its robustness under more general conditions than descents. The work is supported by several results obtained in a high fidelity virtual environment.